Trends in Glucocerebrosides Research: A Systematic Review - Desplanque, Mazarine; Bonte, Marie-Amandine; Gressier, Bernard; Devos, David; Chartier-Harlin, Marie-Christine; Belarbi, Karim (Frontiers in Physiology, 2020)
Glucocerebrosides are sphingolipid components of cell membranes that intervene in numerous cell biological processes and signaling pathways and that deregulation is implicated in human diseases such as Gaucher disease and Parkinson’s disease. In the present study, we conducted a systematic review using document co-citation analysis, clustering and visualization tools to explore the trends and knowledge structure of glucocerebrosides research as indexed in the Science Citation Index Expanded database (1956 – present). A co-citation network of 5324 publications related to glucocerebrosides was constructed. The analysis of emerging categories and keywords suggested a growth of research related to neurosciences over the last decade. We identified ten major areas of research (e.g. clusters) that developed over time, from the oldest (i.e. on glucocerebrosidase protein or molecular analysis of the GBA gene) to the most recent ones (i.e. on drug resistance in cancer, pharmacological chaperones or Parkinson’s disease). We provided for each cluster the most cited publications and a description of their intellectual content. We moreover identified emerging trends in glucocerebrosides research by detecting the surges in the rate of publication citations in the most recent years. In conclusion, this study helps to apprehend the most significant lines of research on glucocerebrosides. This should strengthen the connections between scientific communities studying glycosphingolipids to facilitate advances, especially for the most recent researches on cancer drug resistance and Parkinson's disease.